Market Response to the Weekly Money Supply Announcements in the 1970s - URICH, THOMAS; WACHTEL, PAUL (Journal of Finance, 1981)
ABSTRACT The hypothesis that the weekly announcement of the money supply affects interest rates is examined. The announcement effect is interpreted as a policy anticipation effect. That is, an unanticipated increase in the money supply leads to an increase in interest rates in anticipation of future tightening by the Federal Reserve. Estimates of this effect with proxies for the unanticipated change constructed from a survey of money supply forecasts and an ARIMA model indicate that: (a) financial markets respond very quickly to the announcement; and (b) the response was largest when policymakers emphasized the importance of the monetary aggregates.